MHD Flow And Heat Transfer for the Upper-Convected Maxwell Fluid Over a Stretching/ Shrinking Sheet with Prescribed Heat Flux - Nazila, Ishak; Hasmawani, Hashim; Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Mohd, Khaled; Norhayati, Rosli; Mohd Zuki, Salleh (AIP Publishing, 2015)
In this paper, the effect of Magnetohydrodynamic (MHD) towards the flow and heat transfer for the upper-convected Maxwell (UCM) fluid over a stretching/shrinking sheet with prescribed heat flux (PHF) is considered. The governing equations are transformed into a set of ordinary differential equations (ODEs) by using the similarity transformation. Shooting technique is applied to solve the transform ODEs. Numerical solutions of the local temperature, reduced skin friction coefficient, velocity and temperature profiles are obtained. The features of the flow and heat transfer characteristics for various values of the Prandtl number Pr, the magnetic parameter M, the suction parameter S, the stretching/shrinking parameter and the Maxwell parameter are analyzed and discussed.